PERSEPSI ORANG TUA TERHADAP GAME NUMBER KIDS DALAM PENGAJARAN MATEMATIKA ANAK USIA 5-6 TAHUN. - Kristanti, Valeria Devi; Linarsih, Andini; Amalia, Annisa (Universitas Tanjungpura, 2023)
This study aims to find out about parents' perceptions of number kids games in teaching early childhood aged 5-6 years to stimulate their child's mathematics. Researchers want to see parents' perceptions of the use of 20 choices of mini-games in number kids games for children in mathematics learning from the age of 5-6 years. Research methods used in descriptive methods with qualitative research. The source of data in this study is 20 choices of games in number kids educational games and also parents who have children aged 5-6 years. The data collection techniques used in this study are observation techniques and theme analysis techniques. The data collection tool used in this study adalah questionnaire. Data analysis used using triangulation techniques. The results showed that parents agreed that 20 choices of number kids games can be used for children to teach and to stimulate and teach mathematics to their children aged 5-6 years.